3D Simulation Design and Application of Traditional Hanfu Based on Internet of Things. (30th May 2022) - Lin, Li; Gan, Wen
Abstract : Chinese traditional Hanfu is a kind of clothing that can reflect the changes of Chinese history, culture, and dynasties. With the improvement of people's aesthetic ability and the pursuit of national culture, Hanfu has shown a state of revival. The study of Hanfu has become a research hotspot in today's era. However, there is a big difference between the design of traditional Hanfu and the design of modern clothing. It not only needs to consider people aesthetics and preferences but it also needs to further consider the historical and cultural information represented by traditional Chinese Hanfu. This is a more critical and difficult point for Hanfu designers. If Hanfu cannot be well combined with history and culture, this will easily lead to a misinterpretation of Hanfu. In this study, the feasibility of the 3D simulation design of Hanfu was fully studied by combining the Internet of Things technology and the convolutional neural network method. The research results show that the Internet of Things technology can efficiently and accurately collect the characteristics of patterns, colors, shapes, and historical information of Hanfu. The reliability of IoT technology also improves the accuracy of CNN methods in predicting Hanfu eigenvalues. The largest prediction error is only 2.84%. CNN can also well capture the relationship between historical information features of Hanfu and dynasties, and all predicted feature values are within the 95% confidence interval.